2008
DOI: 10.3141/2086-07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Traveler Information Effects on Commercial and Noncommercial Users

Abstract: Incidents often account for nearly half of traffic congestion in urban areas and add uncertainty to transportation networks. The costs of incident-induced congestion, often in the form of delays, are borne by motorists and commercial carriers or associated businesses. In fact, a higher burden is borne by commercial carriers, given their higher costs and value of time. Dynamic traveler information about incidents disseminated through electronic media can benefit users. The extent of benefits associated with dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, because the dynamic merge system changes as a function of traffic volume, it is difficult to confirm that the difference in merge location of drivers exposed to each merge environment is a direct result of the merge environment itself and not a result of the corresponding traffic levels. Previous research has found that congestion levels influence both route and lane choice (Pan & Khattak, 2008;Xuan & Kanafani, 2014). In fact, traffic volume has been argued to serve as a greater determinant of traveler behavior than information presented on road signs (Xuan & Kanafani, 2014).…”
Section: Dynamic Mergementioning
confidence: 99%
“…However, because the dynamic merge system changes as a function of traffic volume, it is difficult to confirm that the difference in merge location of drivers exposed to each merge environment is a direct result of the merge environment itself and not a result of the corresponding traffic levels. Previous research has found that congestion levels influence both route and lane choice (Pan & Khattak, 2008;Xuan & Kanafani, 2014). In fact, traffic volume has been argued to serve as a greater determinant of traveler behavior than information presented on road signs (Xuan & Kanafani, 2014).…”
Section: Dynamic Mergementioning
confidence: 99%